2003
DOI: 10.1097/01.ogx.0000088884.79233.a8
|View full text |Cite
|
Sign up to set email alerts
|

A 21-Year Longitudinal Analysis of the Effects of Prenatal Alcohol Exposure on Young Adult Drinking

Abstract: Background: Prenatal alcohol exposure may be a risk factor for the development of alcohol problems in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 33 publications
2
78
0
Order By: Relevance
“…Overall, prenatal exposure to alcohol, cigarettes, and street drugs has been reported to be associated with long-term changes in growth and development, neuropsychological deficits, and behavioral sequelae such as increased use of substances in young adulthood (Baer et al, 2003). However, it has not been a common feature of these studies to include other potentially salient causes of these abnormalities such as having a familial diathesis for psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, prenatal exposure to alcohol, cigarettes, and street drugs has been reported to be associated with long-term changes in growth and development, neuropsychological deficits, and behavioral sequelae such as increased use of substances in young adulthood (Baer et al, 2003). However, it has not been a common feature of these studies to include other potentially salient causes of these abnormalities such as having a familial diathesis for psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging question is whether early developmental drug exposure can increase the liability for addictive behaviors later in life. While prenatal exposure to alcohol Baer et al, 2003) and to tobacco Cornelius et al, 2000;Kandel et al, 1994) have been shown in clinical studies to be associated with an increased risk of alcohol and nicotine abuse, respectively, in adolescents and young adults, similar studies on the rate of adolescent or adult drug abuse in cocaine-exposed children have not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with histories of PAE are at increased risk for substance and alcohol abuse problems later in life [Baer et al, 2003;Alati et al, 2008]. Both prevention and intervention programs are needed for this population to provide alcohol-related education to individuals with FASDs and their parents and caregivers (including the risks of drinking during pregnancy), to teach them strategies for avoiding situa-tions and behaviors that may encourage high-risk drinking, and to address ongoing substance and alcohol use/ abuse problems.…”
Section: Substance and Alcohol Abuse Problemsmentioning
confidence: 99%